BMI in childhood and adolescence is associated with impaired reproductive function-a population-based cohort study from birth to age 50 years - Laru, J; Nedelec, R; Koivuaho, E; Ojaniemi, M; Järvelin, M-R; Tapanainen, JS; Franks, S; Tolvanen, M; Piltonen, TT; Sebert, S; Morin-Papunen, L (Human Reproduction, 2021)
STUDY QUESTION: What is the association between childhood and adolescent BMI and reproductive capacity in women? SUMMARY ANSWER: Adolescent girls with obesity had an increased risk of infertility and childlessness in adulthood independently of their marital status or the presence of polycystic ovary syndrome (PCOS). WHAT IS KNOWN ALREADY: Girls with obesity (BMI (kg/m2)>95th percentile) more often exhibit menstrual irregularities and infertility problems as compared to those with normal weight, and premenarcheal girls with obesity have an increased risk of childlessness and infertility in adulthood. Follow-up studies on the relation between childhood and adolescence growth patterns and fertility or parity throughout the reproductive life span are limited. STUDY DESIGN, SIZE, DURATION: A prospective, population-based cohort study (the Northern Finland birth cohort 1966) was performed with 5889 women born in 1966 and followed from birth to age 50 years. Postal questionnaires at ages 31 and 46 years addressed questions on reproductive capacity evaluated by decreased fecundability, need for infertility assessment and treatment by 46 years of age. Childlessness and number of children by age 50 years were recovered from registers. Women who did not report ever having attempted to achieve pregnancy (n = 1507) were excluded. The final study population included 4382 women who attempted to achieve pregnancy before age 46 years. PARTICIPANTS/MATERIALS, SETTING, METHODS: Data on BMI were collected by trained personnel at all stages. We assessed association with both prospectively measured BMI at various time points and with early adiposity phenotypes derived from linear mixed models including the timing and the BMI at adiposity peak (AP) and adiposity rebound (AR). Self-reported infertility assessments and treatments were assessed at ages 31 and 46 years. Data on deliveries were collected from the national birth register. Decreased fecundability was defined at age 31 years as time to achieve pregnancy over 12 months. ...